Analysis of Glucomannan Molecule in Porang (Ammorphophallus Muelleri Blume) Flour using Nuclear Magnetic Resonance: Ivan Rizoputra, Sriati Wahyudi, Niniek Fajar Puspita, Risdiana Risdiana, Darminto Darminto - Ivan Rizoputra Ivan Rizoputra; Sriati Wahyudi Sriati Wahyudi; Niniek Fajar Puspita Niniek Fajar Puspita; Risdiana Risdiana; Darminto Darminto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
The porang tuber (Ammorphophallus Muelleri Blume) is a bulb plant belonging to the Araceae family, which contains the polysaccharide substance of glucomannan. In this work, the porang flour has been purified from tubers by a centrifugation method. To study the content of compounds and types of molecules that make up glucomannan, characterization was carried out using 1H and 13C nuclear magnetic resonance (NMR). The analysis on chemical shift data from both NMR spectra can be concluded that glucomannan in porang is more dominantly constructed by glucose molecules rather than mannose. From these results, it is also known that the toxic compound Ca-oxalate which is part of the porang compound has been reduced during the centrifugation process.